Vascular Surgery in COVID-19 Period and Beyond: Acknowledging the New Normal - Bashyal, Krishnaprasad; Shrestha, Kajan Raj (Journal of Lumbini Medical College, 2020)
The first infected case of Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2) in Nepal was diagnosed on 23 January, 2020 which was also the first recorded case in South Asia, but after confirmation of subsequent cases on March 23 and 24, the entire nation was put under lock down. Between January and March, the government took preventive measures by upgrading health infrastructure, setting up health desks at important public spaces like airports, spreading public awareness through various means, sealing off of international borders. Initially, our optimism stemmed from the slow rise in cases compared to our neighbors which delivered hope that things will be back on track soon. But with consistently escalating infection rates it was clear that we are as vulnerable to this as any other nation. For us, it reflected in thinning out of emergency and urgent cases. This was sure to have a significant impact on patients’ lives. On one hand, owing to confinement measures, to avail specialty services was becoming a challenge for them, especially those from remote, rural areas where transportation even if desired is accessible on select occasions. On the other, phobia of coronavirus led patients to defer going to distant tertiary hospital as far as possible.